In-situ Gelling System for Mucoadhesive Site- Specific Drug Delivery for Treatment of Recurrent Vaginal Candidiasis - Singh, Gurpreet; Shilpa, Shilpa; Ali, Waseem; Sarwal, Amita (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: The purpose of this work was to design and evaluate bio adhesive films for effective treatment against vaginal candidiasis. Fluconazole, a bis tri-azole agent inhibits ergosterol synthesis leading to the disruption of fungal membrane for use as an antifungal agent. The pharmacokinetic profile of fluconazole reveals minimal metabolization, low protein binding and is largely excreted in the urine. Methods: Bioadhesive films were prepared by the solvent evaporation technique. The excipients including chitosan as a mucoadhesive polymer and plasticizer along with polyvinyl alcohol and glycerine were dissolved at a total combined concentration to form optimized formulation. Variables such as swelling index, mucoadhesive strength, percentage drug release, permeation, retention and irritation studies were assessed. Results: The prepared films were generally smooth, pliable and transparent/semi-transparent in appearance having an average thickness range from 0.08±0.005 to 0.15±0.006. In vitro release experiments demonstrated that film formulations exhibited higher drug release in comparison to marketed gel, FLUCOS® with maximum percentage cumulative drug release after 8 hr release of 42.563 ± 0.743%. Skin retention studies were carried out to find the amount of drug retained by the skin layers. Percentage drug retention in porcine vaginal tissue for F13 has been found to be 1.15 and 1.09 times higher than F12 and FLUCOS®. The selected formulation showed an appropriate anti-candida activity through appearance of zone of inhibition during anti-fungal activity studies, with promising results to meet the unmet medical need for vaginal delivery that swells and forms a viscous gel upon insertion into the vaginal cavity. Conclusively, the selected formulation of Intravaginal film creates a mucoadhesive gel that spreads rapidly and widely over the vaginal mucosa and is retained for a sufficiently long time to provide therapeutic efficacy via topical action.
Keywords: Fluconazole; Vaginal film; Mucoadhesive; Vaginal drug delivery; Vulvovaginal candidiasis